Laparoscopic duodenopancreatectomy. Case report - DE VINATEA, JOSÉ (2004)
A case of successful hand-assisted laparoscopic duodenopancreatectomy for duodenal neoplasia is presented. Technical aspects of such procedure is presented as well as pertinent bibliography.